Sepsis risk factor in mount Merapi eruption victims with 2nd or 3rd degree of burn injury - Yamoguna Zega; Ishandono Dachlan (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Sepsis is one of the fatal complications of burns. It is the most common cause of deathfrom burns. Burn sepsis usually occurs after a burn injury develops into infection. Thisstudy was conducted to determine correlation between age, burn area, inhalation trauma,enteral nutrition start time, escarotomy time, and albumin level of sepsis in patientswith 2nd or 3rd degree burn injury. This was a cross sectional study during May to June2012. The subjects in this study were 39 victims of mount Merapi eruption in 2010 whosuffered 2nd or 3rd degree of burns injury. The result showed the correlation betweenwidespread burns, inhalation trauma, time of escarotomy, and albumin levels with sepsis(p < 0.05). In conclusion, the risk factor for sepsis in patients with 2nd or 3rd degree ofburns injury are the area of burns (> 50%), inhalation trauma, time of escarotomy (> 72hours), and albumin levels (<3.5g/dL).